ANALISIS DAN PERANCANGAN SISTEM PENDUKUNG KEPUTUSAN PENENTUAN PRIORITAS PERBAIKAN JALAN PADA PEMERINTAH DAERAH KABUPATEN BATANG HARI DENGEN METODE AHP (ANALYTICAL HIERARCHY PROCESS) - Kurniawan, Irwan; Assegaff, Setiawan (LPPM Universitas Dinamika Bangsa, 2019)
The road is an infrastructure that plays an important role in people's daily lives. Therefore, it isnecessary to maintain and repair road conditions regularly. The existence of budget constraints causesnot all damaged road sections can be handled. So that in handling road repairs it is necessary todetermine priorities. In determining the priority of road improvement there are criteria that are takeninto consideration in decision making. One method of analysis that can be used to overcome complexitydue to various criteria is the Analytical Hierarchy Process (AHP) method. The AHP method is used toobtain the weight of 4 criteria that are taken into consideration in determining the priority of roadimprovement, namely road conditions, traffic volume, costs, and road classification. Calculation of scoresfor each road improvement proposal is obtained by multiplying the priority weight of the criteria by thecriteria value of each proposal. The results show that the Decision Support System that is designed canproduce a ranking of alternatives in the form of road improvement proposals based on predeterminedcriteria, so that it can be used as a basis for decision making to determine road improvement priorities.